Peran Gerakan Oikumene Terhadap Pembangunan Perdamaian Dan Toleransi di Indonesia - Helma Mesya Cristiani Br Siregar; Meditatio Situmorang (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Indonesia is a country with high religious, cultural and ethnic diversity, where the potential for conflict and intolerance often becomes a challenge in social life. In this context, the Ecumenical Movement plays a strategic role as a forum for Christian unity across denominations to support the development of peace and tolerance in Indonesia. Through an approach to inter-religious dialogue, inclusive education and social action, this movement contributes to strengthening social harmony and building cross-religious solidarity. The Ecumenical Movement succeeded in reducing inter-religious prejudice, promoting respect for diversity, and forming a tolerant young generation. The Ecumenical Movement not only plays a role in strengthening internal relations among Christians but is also an important actor in creating peace and social stability in Indonesia's multicultural society.